Targeting Macrophage Phenotype for Treating Heart Failure: A New Approach - Shi M; Yuan H; Li Y; Guo Z; Wei J (Dove Medical Press, 2024)
Min Shi,1,2,* Hui Yuan,2,3,* Ya Li,4 Zhihua Guo,2,3 Jiaming Wei1,2 1School of Chinese Medicine, Hunan University of Chinese Medicine, Changsha, 410208, People's Republic of China; 2Hunan Key Laboratory of Colleges and Universities of Intelligent TCM Diagnosis and Preventive Treatment of Chronic Diseases, Hunan University of Chinese Medicine, Changsha, 410208, People's Republic of China; 3First Clinical College of Chinese Medicine, Hunan University of Chinese Medicine, Changsha, 41020, People's Republic of China; 4School of Pharmacy, Hunan University of Chinese Medicine, Changsha, 410208, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhihua Guo; Jiaming Wei, Hunan University of Chinese Medicine, 300 Xue Shi Road, Hanpu Science & Education Park, YueLu District, ChangSha, 410208, People's Republic of China, Email 004294@hnucm.edu.cn; 004916@hnucm.edu.cnAbstract: Heart failure (HF) is a disease with high morbidity and mortality rates worldwide and significantly affects human health. Currently, the treatment options for HF are limited, and there is an urgent need to discover new therapeutic targets and strategies. Macrophages are innate immune cells involved in the development of HF. They play a crucial role in maintaining cardiac homeostasis and regulating cardiac stress. Recently, macrophages have received increasing attention as potential targets for treating HF. With the improvement of technological means, the study of macrophages in HF has made great progress. This article discusses the biological functions of macrophage phagocytosis, immune response, and tissue repair. The polarization, pyroptosis, autophagy, and apoptosis are of macrophages, deeply involved in the pathogenesis of HF. Modulation of the phenotypic changes of macrophages can improve immune-inflammation, myocardial fibrosis, energy metabolism, apoptosis, and angiogenesis in HF. Keywords: heart failure, macrophage, polarization, pyroptosis, apoptosis, autophagy